2005
DOI: 10.1002/ar.a.20185
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic cerebrospinal fluid regulates neuroepithelial survival, proliferation, and neurogenesis in chick embryos

Abstract: Early in development, the behavior of neuroepithelial cells is controlled by several factors, which act in a developmentally regulated manner. Diffusible factors are secreted locally by the neuroepithelium itself, although other nearby structures may also be involved. Evidence suggests a physiological role for the cerebrospinal fluid in the development of the brain. Here, using organotypic cultures of chick embryo neuroepithelial explants from the mesencephalon, we show that the neuroepithelium in vitro is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(147 citation statements)
references
References 56 publications
11
131
1
4
Order By: Relevance
“…Many such signals have been found in fetal CSF (fCSF), indicating that fCSF is part of the neurogenic niche (Owen-Lynch et al, 2003;Gato et al, 2005;Miyan et al, 2006;Johanson et al, 2008Johanson et al, , 2011Gato and Desmond, 2009). Two proteomic analyses of fetal CSF of rats and humans have revealed numerous compounds that likely are cues for diff erent phases of neurogenesis (Parada et al, 2005;Zappaterra et al, 2007).…”
Section: Alterations Of the Microenvironment Of The Neu-rogenic Nichementioning
confidence: 99%
“…Many such signals have been found in fetal CSF (fCSF), indicating that fCSF is part of the neurogenic niche (Owen-Lynch et al, 2003;Gato et al, 2005;Miyan et al, 2006;Johanson et al, 2008Johanson et al, , 2011Gato and Desmond, 2009). Two proteomic analyses of fetal CSF of rats and humans have revealed numerous compounds that likely are cues for diff erent phases of neurogenesis (Parada et al, 2005;Zappaterra et al, 2007).…”
Section: Alterations Of the Microenvironment Of The Neu-rogenic Nichementioning
confidence: 99%
“…Moreover, lineage tracing showed colonies cocultured with endothelial cells continued to undergo expansive symmetric divisions and lacked asymmetric neuron-generating divisions seen in neural stem cell colonies alone (Shen et al, 2004). CSF has been shown to maintain the survival, proliferation, and differentiation of neuroepithelial cells in vitro (Gato et al, 2005;Miyan et al, 2006). Furthermore, a recent in vivo study that drained the CSF and administered BrdU found a marked decrease in proliferation 3 days after analysis and suggests a role of the CSF in regulating neural stem/precursor cell proliferation (Mashayekhi and Salehi, 2006).…”
Section: Similarities and Differences Between Adult And Fetal Neural mentioning
confidence: 99%
“…Growing evidence suggests that CSF plays an important role not only in brain development but also in survival and proliferation of neuroectodermal stem cell (13). A previous study showed that adult CSF facilitates gliogenesis from the fetal rat neural stem cell (5).…”
Section: Immediately After Electrophysiological Evaluation Middlementioning
confidence: 99%